Opportunities and challenges of strategic planning in the context of circular economy: an exploratory analysis - Ferrari, Aline Gabriela; Jugend, Daniel [UNESP]; Armellini, Fabiano; Seles, Bruno Michel Roman Pais (Emerald, 2025)
Purpose: This study aims to explore relationships between strategic planning and the adoption of the circular economy (CE), addressing a gap in current research about the role strategic planning plays in supporting the implementation of CE. Design/methodology/approach: To achieve the objective of this research, case studies were conducted at four Canadian companies with well-established environmental sustainability strategies. Findings: The findings highlight the importance of engaging both internal and external stakeholders in facilitating knowledge exchange, as it is essential for strategic planning in CE initiatives. Additionally, the commitment of companies to circularity principles and the use of formal strategic planning tools are identified as valuable assets in the integration process. The study also presents and analyzes the challenges of integrating CE into companies’ strategic planning. Originality/value: This study contributes to the existing literature by shedding light on the interplay between strategic planning and CE adoption, offering insights into the complexities and opportunities involved in integrating CE principles into organizational strategies. A framework for the integration of CE into strategic planning is also proposed.
Keywords: Circular economy; Collaboration; Environmental sustainability; Strategic tools; Strategy